Dynamic changes and improvement paths of China’s emergency logistics response capabilities under public emergencies—research based on the entropy weight TOPSIS method - Chen, Heng; Guo, Yuan; Lin, Xianglong; Qi, Xianchao (Frontiers in Public Health, 2024)
In order to identify the changes and enhancement paths of the emergency logistics response capability of Chinese regions under the shocks of public emergencies, this paper innovatively constructs emergency logistics response capability measurement indicators. This paper uses the entropy weight TOPSIS method and panel quantile regression model to quantify the change and enhancement paths of China's regional emergency logistics response capability under different events. It is found that: (1) The gap in emergency logistics response capability among Chinese regions is widening, with the internal difference in the eastern region higher than that in the west, while the difference in the central region is relatively low.(2) China's emergency management department can effectively transform social logistics into emergency logistics, thereby promoting the improvement of emergency logistics response capabilities.(3) Sudden geological disasters break through the limits of social logistics resources when they cross lower scales, resulting in the failure of emergency logistics response capabilities.With the accelerated industrialization and urbanization of the world, as well as the deterioration of the atmospheric and geological environments, a variety of natural disasters, accidents, catastrophes and public health events have occurred frequently. This has caused huge casualties and heavy property losses to countries around the world. Compared with most countries, China is one of the few countries with the most serious natural disasters. According to the data for 2020, China was affected by public emergencies, causing 138 million victims and direct economic losses amounting to 370.145 billion yuan, accounting for 0.375% of GDP.Therefore, how to closely prevent and effectively respond to the losses caused by various types of public emergencies. This has become a matter of close attention for countries around the world. Moreover, Domestic and foreign governments and academia generally believe that"building a hierarchical response system for emergency logistics is an important safeguard